2019
DOI: 10.20473/j.djmkg.v52.i2.p100-104
|View full text |Cite
|
Sign up to set email alerts
|

Permanent tooth eruption based on chronological age and gender in 6-12-year old children on Madura

Abstract: Background: Tooth eruption, the movement of teeth toward the oral cavity clinically marked by the emergence of the cusp or incisal edge, is very important in determining the chronological age of a child. Unfortunately, tooth eruption in 6-12-year olds on the island of Madura has yet to be investigated. Purpose: This study aimed to analyze differences in permanent tooth eruption between boys and girls aged 6 to 12 years old on Madura. Methods: This study employed an observational analytic design in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
2
Order By: Relevance
“…Hasil penelitian yang dilakukan oleh Marjianto, dkk (2019) tentang erupsi gigi permanen berdasarkan usia kronologis dan jenis kelamin pada anak usia 6-12 tahun di Madura menujukkan bahwa gigi tetap pada jenis kelamin perempuan secara kronologis pada usia 6-12 tahun erupsi lebih awal daripada anak dengan jenis kelamin laki-laki. Erupsi paling awal terjadi pada gigi kaninus mandibula permanen anak perempuan (15) .…”
Section: Pembahasanunclassified
“…Hasil penelitian yang dilakukan oleh Marjianto, dkk (2019) tentang erupsi gigi permanen berdasarkan usia kronologis dan jenis kelamin pada anak usia 6-12 tahun di Madura menujukkan bahwa gigi tetap pada jenis kelamin perempuan secara kronologis pada usia 6-12 tahun erupsi lebih awal daripada anak dengan jenis kelamin laki-laki. Erupsi paling awal terjadi pada gigi kaninus mandibula permanen anak perempuan (15) .…”
Section: Pembahasanunclassified
“…The diagnosis is based on the missing teeth and the space analysis of Moyers, Huckaba, and Arch Determination. This refers to the theory highlighting that the effects of tooth eruption and the number Advances in Health Sciences Research, volume 33 of abnormalities that may occur in the oral cavity will help dentists determine the appropriate diagnosis and therapy [20] .…”
Section: Discussionmentioning
confidence: 99%
“…There were 14 studies found from the conducted search, which summarized in Table 1. The age coverage of the most study was young adult and children (71%) [11][12][13][14][15][16][17][18][19][20] . Only three studies which involved age range more than 25 years [21][22][23] .…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
“…The most age estimation method applied in Indonesian population was Demirjian's method, with or without modification (35.71%) 11,12,15,16,21 , followed by TCI-Benindra's method (21.42%) [18][19][20] , and the other methods (7.14%-13%), as presented in Figure 1. Panoramic radiograph was the most used sample for the studies (53%) 11,12,[15][16][17][18][19][20][21]23 , followed by clinical examination (17%) 13,14,24 , periapical radiograph (12%) 18,19 , lateral cephalometric radiograph (12%) 18,19 , and CBCT (6%) 22 (Figure 2).…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
See 1 more Smart Citation